THE COMPARISON OF TWO TYPES COMPOSITE RESIN PACKABLE NANOHYBRID WITH TOTAL ETCH BONDING IN CLASS V RESTORATION MICROLEAKAGE - Sari Dewiyani; Denissa Zahra S. (Moestopo International Review on Social, Humanities, and Sciences, 2021)
At dental clinic, there are some obstacles which occasionally may occur. A dentist runs out of the same brand of the composite resin and bonding material during tooth restoration, so they would have to be paired with material of the diffrent brand. Certain things that may occur during tooth restoration is polymerization shrinkage which forms a gap that could reducing edge density. This research is using packable nanohybrid type A composite resin and packable nanohybrid type B resin composite with total etch bonding on Class V restoration with the thin cervical section of enamel. Aim: This research is to explain the differences between two types of packable nanohybrid composite resins with total etch bonding in Class V microleakage. Methods: This research will use an experimental laboratory method with 32 maxillary premolars that have been prepared in Class V, which divided into 2 groups, group A and group B. Methylene blue will be used for the measurements, whereas the microscope will be used for the observation. Furthermore, data analysis would be conducted using the Mann Whitney U Test Method. Results: The research showed that there was a significant difference between group A and group B, which is p <0.05. Conclusion: According to this research, it can be seen that group B showed less leakage compared to group A.